Acute Pericarditis in Patient with Systemic Lupus Erythematosus: A Case Report - Anudya Kartika Ratri; Mochamad Yusuf Alsagaff; Tri Pudy Asmarawati (Jurnal Kardiologi Indonesia, 2018)
Acute pericarditis is a common disorder caused by inflammation of the pericardium and can occur as an isolated entity or as a manifestation of an underlying systemic disease. The diagnosis of acute pericarditis is established when a patient has at least two of the following symptoms or signs: chest pain consistent with pericarditis, pericardial friction rub, typical ECG changes, or a pericardial effusion of more than trivial size. Systemic Lupus Erythematosus (SLE) is a chronic autoimmune systemic disorder with unknown etio-pathogenesis. Upon the susceptible genetic, hormonal and abnormal immunologic background, the environmental factors may play role as trigger to permit disease development. Cardiovascular complications occur in more than half of the patients with SLE. Pericarditis is the most studied cardiovascular manifestation, although often not evident clinically, and it is included in the American College of Rheumatology (ACR) classification criteria for SLE. We report a clinical case of initially unremarkably findings which progressed to SLE complicated by full-blown acute pericarditis. A brief review of acute pericarditis, including etiology, clinical presentation, ECG criteria, echocardiographic manifestation, and treatment is presented. Abstrak Perikarditis akut adalah penyakit yang disebabkan oleh inflamasi dari perikard, dapat terjadi sebagai entitas penyakit primer maupun sekunder sebagai manifestasi dari penyakit sistemik yang mendasarinya. Diagnosis perikarditis akut ditegakkan saat pasien mengalami setidaknya dua dari tanda atau gejala berikut: nyeri dada spesifik perikarditis, pericardial friction rub, perubahan EKG tipikal, atau adanya efusi perikard dengan ukuran lebih dari trivial. Lupus Eritematosus Sistemik (LES) adalah penyakit autoimun sistemik kronis dengan etiopatogenesis yang belum diketahui. Adanya kepekaan genetik, latar belakang imunologis abnormal dan hormonal, serta faktor lingkungan memegang peran sebagai pemicu perkembangan penyakit. Komplikasi kardiovaskular terjadi pada lebih dari setengah pasien dengan SLE. Perikarditis merupakan manifestasi kardiovaskular yang paling sering dijumpai, meskipun jarang ditemukan patognomonis secara klinis, dan termasuk dalam kriteria klasifikasi LES menurut American College of Rheumatology (ACR). Berikut kami laporkan kasus dengan presentasi klinis febris dan takikardia yang kemudian mengarah pada LES dengan komplikasi perikarditis akut. Kami sertakan juga ulasan tentang perikarditis akut, termasuk etiologi, presentasi klinis, kriteria EKG, manifestasi ekokardiografis, dan terapi.